Antibodies to the α1-adrenergic receptor cause vascular impairments in rat brain as demonstrated by magnetic resonance angiography. - Peter Karczewski (Public Library of Science (PLoS), 2012)
Background Circulating agonistic autoantibodies acting at G protein-coupled receptors have been associated with numerous sever pathologies in humans. Antibodies directed predominantly against the α(1)-adrenergig receptor were detected in patients suffering from widespread diseases such as hypertension and type 2 diabetes. Their deleterious action has been demonstrated for peripheral organs. We postulate that antibodies to the α(1)-adrenergig receptor are relevant pathomolecules in diseases of the central nervous system associated with vascular impairments. Methodology/principal findings Using a rat model we studied the long-term action of antibodies against the α(1)-adrenergig receptor either induced by immunization with a receptor peptide or applied by intravenous injection. The vasculature in the rat brains was investigated by time-of-flight magnetic resonance angiography using a 9.4 Tesla small animal MR imaging system. Visual examination of maximum-intensity-projections (MIPs) of brain angiographs revealed the development of vascular defects in antibody- exposed animals between three and eight months of treatment. Relative vascular areas were derived from representative MIP image sections by grayscale analysis and used to form an index of vascular circulation. Animals exposed to the action of α(1)-adrenergig receptor antibodies showed significantly reduced vascular areas (p<0.05). Calculated index values indicated attenuated blood flow in both antibody-treated cohorts compared to their respective controls reaching with (relative units ± standard error, n = 10) 0.839 ± 0.026 versus 0.919 ± 0.026 statistical significance (p<0.05) for peptide-immunized rats. Conclusion/significance We present evidence that antibodies to the α(1)-adrenergig receptor cause cerebrovascular impairments in the rat. Our findings suggest the pathological significance of these antibodies in pathologies of the human central nervous system linked to impairments of brain vasculature such as stroke and dementia.